Pengaruh Terapi Relaksasi Lima Jari dan Senam Hamil Terhadap Kecemasan pada Kehamilan Trimester 3 Menjelang Persalinan di PMB Ny. M di Kabupaten Cianjur Tahun 2024 - Butet Agnes Melani Sinaga; Retno Sugesti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The third trimester of pregnancy, especially towards delivery, is a crucial phase for expecting mothers. Anxiety during this period is a common emotional response, which can affect both maternal and fetal health. This study aims to assess the effects of relaxation therapy using the "Five-Finger Relaxation" technique and pregnancy exercises (senam hamil) on anxiety levels in pregnant women in their third trimester, nearing labor, at PMB Ny. M in Cianjur District in 2024. The study uses a pre-experimental one-group pretest-posttest design, involving 30 pregnant women as participants. Data were collected using the State-Trait Anxiety Inventory (STAI) questionnaire and analyzed using descriptive statistics and the paired t-test to compare anxiety levels before and after the interventions. The results indicate that both Five-Finger Relaxation therapy and pregnancy exercises significantly reduce anxiety levels in the participants, with a p-value < 0.05. These findings suggest that combining these two interventions can be an effective and simple strategy to reduce anxiety in pregnant women in the third trimester. Therefore, it is recommended to integrate these therapies into routine prenatal care as part of comprehensive maternal health management..